Performance of large firms in Greece during the unstable period of 2011-2016: Lessons from the weak parts of Europe - Maria Tsiapa (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - The unprecedented economic crisis in Greece deeply affected entrepreneurship, which was traditionally characterised by low levels of innovation and competitiveness, the dominant presence of micro-sized enterprises and the weak signs of prosperity in large firms. This paper, in acknowledgement of the necessary transformations that production incurred due to the crisis, attempts to detect the characteristics of large manufacturing firms that contributed to their greater resilience during the unstable period of 2011-2016 by analysing the determinants of the higher profitability of firms. The analysis shows that firms that improved their productivity and sales levels and in parallel are flexible, in the sense that they have limited amounts of both assets and liabilities and thus a small risk, are those that presented higher profits during the period under study. Initial conditions, sectoral characteristics and the broader national environment do not seem to have a strong contributive role in firms' profitability. Design/methodology/approach - The analysis follows a dynamic system generalised method of moments (GMM) estimation based on a panel data set of 125 Greek large firms over the time span 2011-2016. Findings - The analysis shows that firms that improve their productivity and sales levels and in parallel are flexible, in the sense that they have a limited amount of both assets and liabilities and thus a small risk, are those that present higher profits during the period under study. Initial conditions, sectoral characteristics and the broader national environment do not seem to have a strong contributive role in firms' profitability. Research limitations/implications - The present paper attempts to explain the performance of the most dynamic large manufacturing firms in Greece by investigating the role of some of the most important determinants of firm profitability (according to data availability), acknowledging, however, some analysis' limitations as the absence of some other parameters like the export activity or the incorporation of any innovative features in the firms Originality/value - The novelty of this paper lies in two points. First, the subject of the analysis is the large firms in Greece, which have not received much attention as Greek entrepreneurship was traditionally based on the light, labour- or resource-intensive production and the main bulk of the literature was not on that topic. Second, during the deep and protracted crisis that Greece has experienced, several production transformations have taken place that remain partly undiscovered. The present paper attempts to analyse the characteristics of large firms that drove their profitability and improved their resilience during the crucial time period 2011-16.
Keywords: 650; Economic crisis; Greece; Large firms; Profitability